Enhancing photocurrent performance based on photoanode thickness and surface plasmon resonance using Ag-TiO2 nanocomposites in dye-sensitized solar cells - Lokman, Muhammad Quisar; Shafie, Suhaidi; Shaban, Suraya; Ahmad, Fauzan; Jaafar, Haslina; Mohd Rosnan, Rizuan; Yahaya, Hafizal; Abdullah, Shahrum Shah (MDPI, 2019)
This study investigated the different thicknesses of TiO2 photoanode films and the effect of surface plasmon resonance (SPR) of Ag-TiO2 nanocomposites on the current-voltage (I–V) performance of dye-sensitized solar cells (DSSC). The TiO2 layer was deposited using the doctor blade technique and the thickness of the TiO2 films was controlled by using a different number of Scotch tape layers. The silver nanoparticles (AgNP) were synthesised using a chemical reduction method and the concentration of sodium citrate as a reducing agent was varied from 4 to 12 mM to study the effect of citrate ion on the size of the nanoparticles. Ag-TiO2 nanopowder was prepared by adding pure anatase TiO2 powder into AgNP colloidal solution. The mixture was left to dry for 24 h to obtain Ag-TiO2 powder for paste preparation. The three-layer Scotch tape, with thickness of 14.38 µm, achieved a high efficiency of 4.14%. This results showed that three layers was the optimal thickness to improve dye loading and to reduce the charge recombination rate. As for the Ag-TiO2 nanocomposites, 10 mM of AgNP, with a mean diameter of 65.23 nm and high efficiency of 6.92%, proved that SPR can enhance the absorption capability of dye and improve the photon-to-electron generation.